Metamorphic record in metalherzolite pockets within the Virsini metaharzburgite from the Kechros HP metamorphic complex in Eastern Rhodope, Greece. - Mposkos, E.; Perraki, M. (Bulletin of the Geological Society of Greece, 2013)
The Virsini antigorite serpentinite from the Kechros HP metamorphic complex in eastern Rhodope is a serpentinized harzburgite with pockets of lherzolitic composition. In the metalherzolites the mantle assemblage is Ol-1+Opx+Cpx-1+Cr-Spl. The metamorphic assemblage is Atg+Ol-2+Cpx-2+Ol-3+Chl+Tr+Cr-Mag. Antigorite and Cr-magnetite formed in an early stage of the metamorphic event. With increase in metamorphic grade olivine (Ol-2) was formed at the expense of antigorite and with further increase tremolite, olivine (Ol-3) and chlorite were formed at the expense of clinopyroxene and antigorite. P-T conditions of ≈1.7 GPa/≈570 oC are recorded in neighbouring eclogites. For the temperature of 570 oC the reaction Di+Atg→Ol+Tr+H2O occurs at pressure of 1.2 GPa suggesting that the stability field of the mineral assemblage Atg+Ol+Tr in the metalherzolite is crossed during decompression.